Persistent Postoperative Hiccups - Emily Bryer; Jeffrey Bryer (Case Reports in Anesthesiology)
Hiccups are a common and poorly understood pathologic phenomenon. While hiccups often occur suddenly and episodically, they may persist for weeks and sometimes months. There is a paucity of data regarding the precise etiology and optimal treatment for persistent hiccups. Frequently considered a benign and frustrating condition, hiccups are sometimes a presenting symptom for pulmonary embolism and cardiac disease. We present a patient with gastroesophageal reflux disease who developed 11 days of recurrent hiccups following an orthopedic procedure.